The Oxford handbook of social movements - Della Porta, Donatella, 1956-; Diani, Mario, 1957- (London Oxford University Press, 2017)
The Oxford handbook of social movements' is an innovative volume that presents a comprehensive exploration of social movement studies, mapping the field and expanding it to examine the recent developments in cognate areas of studies, within and beyond sociology and political science. This volume brings together the most distinguished social and political scientists working in this field, each writing thought-provoking essays in their area of expertise, and facilitates conversations between classic social movement agenda and lines of research. 'The Oxford handbook of social movements' discusses core theoretical perspectives, recent contributions from the field, and how patterns of macro social change may affect social movements, as well as suggesting what contributions social movement studies can give to other research areas in various disciplines
Keywords: Movimientos sociales -- Historia; Estructura social; Cambio (Sociología)